A Review of Pioneer Physicians' Work on Maternal Health in Pregnancy in Ancient Iran; Narrative Systematic Review. - Effat Jafari-Dehkordi; Roshanak Mokaberinejad; Bagher Minaei; Farnaz Sohrabvand; Esmaeil Nazem; Fataneh Hashem Dabaghian; Jale Aliasl (Tehran University of Medical Sciences, 2013)
Background Maternal lifestyle and behaviors during pregnancy have been associated with future health outcomes for mothers and babies. Iranian Traditional medicine, which is a holistically-oriented medical discipline, has special attitudes towards pregnancy. The purpose of the study is the investigation of maternal health in medical books of ancient Iran. This study is a systematic review scrutinizing issues concerning lifestyle during pregnancy based on "Avicenna's Canon medicine" and "Rhazes Al-Havi" and for complete discussion, other reliable sources in traditional medicine which was conducted following the categorization and analysis of the gleaned data. Based on approaches by Iranian Traditional Medicine, the most important topics in lifestyle habits during pregnancy are divided into four main groups: Nutrition, physical exercise, sexual activity and psychological stress. Then special recommendations are suggested which include a regimen to facilitate labor. Eating behaviors and other lifestyle habits have a major role in optimizing the health of women in pregnancy. Regarding to traditional medicine viewpoints paying special attention to correcting diet, life style and preventive attitude with effective and simple therapeutic procedures, it seems that traditional medicine can offer efficient managements to alleviate some pregnancy complications.